From temporary help jobs to permanent employment: what can we learn from matching estimators and their sensitivity? - Andrea Ichino; Fabrizia Mealli; Tommaso Nannicini (Institute for the Study of Labor (IZA), 2006)
The diffusion of Temporary Work Agency (TWA) jobs originated a harsh policy debate and ambiguous empirical evidence. Results for the US, based on quasi-experimental evidence, suggest that a TWA assignment decreases the probability of finding a stable job, while results for Europe, based on the Conditional Independence Assumption (CIA), typically reach opposite conclusions. Using data for two Italian regions, we use a matching estimator to show that TWA assignments can be an effective springboard to permanent employment. We also propose a simulation-based sensitivity analysis, which highlights that only for one of these two regions our results are robust to specific failures of the CIA. We conclude that European studies based on the CIA should not be automatically discarded, but should be put under the scrutiny of a sensitivity analysis like the one we propose.
Keywords: C2; C8; J6; 330; matching estimation; temporary employment; Arbeitsmarkt; Arbeitslosigkeit; Leiharbeit; Beschäftigungseffekt; Arbeitsplatzsicherung; Italien; Toskana; Sizilien